Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Driver Go-Ride pada Masa Pandemi Covid-19 di Gorontalo - Usman Usman (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
Online transportation is a means of transportation based on a particular application, where consumers order transportation through the application system on a smartphone which makes it very easy for users. This study aims to examine and analyze the effect of incentives on Go-Ride drivers, the effect of input from service transactions on Go-Ride drivers and to see the effect of flextime on drivers on Go-Ride in Gorontalo. The research method used is quantitative research methods. The research subjects in this study were Go-Ride drivers who were active in Gorontalo. The sample in this study was determined based on incidental sampling. The data analysis technique used by researchers is multiple regression analysis with partial hypothesis testing, namely the t test and the coefficient of determination (Adjusted R Square). The results showed that incentives have a positive effect on driver's income on Go-Ride in Gorontalo, the number of service transactions that affect driver's income on Go-Ride in Gorontalo and Flextime have a positive effect on drivers on Go-Ride in Gorontalo. The acquisition of a determinant value (Adjusted R Square) of 65.3% for Go-Ride drivers in Gorontalo. While the rest amounted to 34.7%. By other variables not included in this study